1997
DOI: 10.1002/(sici)1099-1018(199701)21:1<1::aid-fam583>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melting Behaviour on Upward Flame Spread of Thermoplastics

Abstract: The effect of melting behaviour on upward flame spread of thermoplastic materials when subjected to small ignition sources and considered to suffer no external flux was studied using large‐scale tests. For moderate fire conditions the cone calorimeter was utilized, with the sample set in a vertical orientation to study the melting behaviour of the specimens. Under these conditions the results indicate that the melting behaviour significantly affects upward flame spread behaviour. A pool of the melt which forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 0 publications
2
45
0
1
Order By: Relevance
“…The melting and dripping phenomena have been recognized as important factors affecting the fire dynamics of thermoplastics . On the one hand, the flowing of un‐ignited polymer melt removes fuel and heat.…”
Section: Introductionmentioning
confidence: 99%
“…The melting and dripping phenomena have been recognized as important factors affecting the fire dynamics of thermoplastics . On the one hand, the flowing of un‐ignited polymer melt removes fuel and heat.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [3] pointed out that the flowing pool fires induced by molten thermoplastic play a significant role in the fire spread. It is also suggested that the pool fires supply an additional heat source to the upward flame spread.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [3,4] claimed that the flame spread was eventually controlled by the pool fire formed at the base of a solid polymer. Sherratt and Drysdale [5] confirmed this discovery and reported the importance of flooring material in pool fire development.…”
Section: Introductionmentioning
confidence: 99%